The role of territory branding in university development of international relations - Viktoriya A. Pulkina; Georgy V. Korshunov (Высшее образование в России)
The key theme of the article is the possibility of higher school promotion and developmentof its international relations through the image of the territory where it is located. The authors describe new media in the Internet as the main channel of communication with foreign target audiences for involvement of useful migrants – students, scientists, teachers, the partner companies to Ukhta. That strategy can contribute much to formation of the attractive image of the city.